Opinion Dynamics via Search Engines (and other Algorithmic Gatekeepers) - Fabrizio Germano; Francesco Sobbrio (Center for Economic Studies and ifo Institute (CESifo), 2017)
Ranking algorithms are the information gatekeepers of the Internet era. We develop a stylized framework to study the effects of ranking algorithms on opinion dynamics. We consider rankings that depend on popularity and on personalization. We find that popularity driven rankings can enhance asymptotic learning while personalized ones can both inhibit or enhance it, depending on whether individuals have common or private value preferences. We also find that ranking algorithms can contribute towards the diffusion of misinformation (e.g., “fake news”), since lower ex-ante accuracy of content of minority websites can actually increase their overall traffic share.
Keywords: D83; L86; 330; search engines; ranking algorithm; search behavior; opinion dynamics; information aggregation; asymptotic learning; misinformation; polarization; website traffic; fake news